2016
DOI: 10.1002/jclp.22374
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Association Between Negative Life Events and Suicidal Risk in College Students: Examining Self‐Compassion as a Potential Mediator

Abstract: These findings suggest that there are specific facets of self-compassion that account for the association between NLE and suicidal risk in college students and that (loss of) common humanity plays a central role in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…The combined sample size was 4,345 participants, with a mean age of 20.9 years old (range = 11–66 years old); 58.6% ( n = 2,547) of participants were female. Five studies were conducted in North America (Chang et al, ; Gregory et al, ; Hayes et al, ; Rabon, Sirois, & Hirsch, ; Tanaka et al, ) and were the only studies to detail ethnicity; three of the samples were predominantly White (59–89%) and female (67.9–100% female). Tanaka et al's () sample reported diverse ethnic backgrounds (27% White, 31.3% Black, and 27.8% dual/multiple ethnicity).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined sample size was 4,345 participants, with a mean age of 20.9 years old (range = 11–66 years old); 58.6% ( n = 2,547) of participants were female. Five studies were conducted in North America (Chang et al, ; Gregory et al, ; Hayes et al, ; Rabon, Sirois, & Hirsch, ; Tanaka et al, ) and were the only studies to detail ethnicity; three of the samples were predominantly White (59–89%) and female (67.9–100% female). Tanaka et al's () sample reported diverse ethnic backgrounds (27% White, 31.3% Black, and 27.8% dual/multiple ethnicity).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies assessed a variety of outcomes, including suicidal ideation (Beck Scale for Suicidal Ideation; Beck & Steer, in Collett et al, ) and self‐harm (Risk‐taking and Self‐harm Inventory for Adolescents Portuguese; Xavier et al, in Xavier et al, ). Two studies (Chang et al, ; Rabon et al, ) assessed mixed suicidal behaviours (Suicidal Behaviours Questionnaire‐revised [SBQ‐R]; Osman et al, ). Jiang et al () assessed the frequency of NSSI methods used in the preceding 12 months with responses on a Likert‐type scale ranging from 1 ( never ) to 7 ( almost every day ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-esteem is built on standards/norms established by the outside world; self-compassion means providing non-judgmental understanding of one's own pain, inadequacies and failures (Neff 2003). Self-compassion can mediate the influence of negative life-events and thereby reduce the risk of suicide (Chang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Low self-compassion is related to mental suffering in college students, including depression (Neff, 2011), sadness, anxiety, anger, and embarrassment (Leary et al, 2007). Self-compassion is a significant mediator between negative life experiences and suicidal tendency, as indicated by depressive sighs and suicidal actions (Chang et al, 2016). As the distress levels of college students continue to rise and university counseling centers struggle to meet these demands, it is important to reexamine and develop resources that better meet the mental health needs of these college students.…”
Section: Introductionmentioning
confidence: 99%